Geoscience Outreach:: Raising Awareness of Earth Science through the BC Year of Science 2010–2011 - Van der Flier-Keller, Eileen (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2011)
SUMMARY The British Columbia Year of Science (YoS), held in 2010–11, was a provincial government–science community collaboration aimed at engaging youth in science. The YoS provided a timely opportunity to expand our Earth science outreach efforts in British Columbia. Key components of the three initiatives reported on below include university student engagement, collaboration with partners (both within the university and in government and community sectors), funding from a variety of sources, and a target audience of primarily youth, their teachers and parents. The first project, Earth Science and Society, involved K–12 classroom presentations (127 to 2615 students), teacher and educator workshops (8 to ~138 participants) and community events (15, audience of ~ 1238). Of the K–12 students surveyed, 89.8% indicated that because of the presentations they wanted to learn more about science. In the second project, Earth science was an important part of one of the four YoS signature Expos, ‘Science and the World Around Us’ held in Prince George with over 3000 youth and community participants. The third project, ‘Science in our Lives’, involved development of nine societally relevant hands-on activities (4 involving aspects of Earth science) that were posted on [http://uvic.ca/sciweb/], together with 21 scientist-career profiles. The latter, featured as ‘5 Minutes with a Scientist’, highlighted exciting relevant careers in science, and portrayed scientists as real, approachable people doing interesting things that they are passionate about. Key successes of these outreach efforts include: i) funding from multiple sources enabling us to recruit and support four undergraduate students to participate in a broad-ranging outreach program; ii) partnerships and collaborations developed with government, the community and within the university; and iii) legacy resources, including activities, career profiles, teacher workshop manuals, and a new school program in non-renewable resources developed with Capital Region District Victoria to supplement their 3R sustainability school program offerings.